Synthesis of Ruthenium Complex Based on 2,6-Bis(1-(phenyl)-1H-benzo[d]imidazol-2-yl)pyridine and 2-(1-Phenyl-1H-benzo[d]imidazol-2-yl)benzoate and Catalytical Oxidation Property of 1-(1H-Benzo[d]imidazol-2-yl)ethanol to 1-(1H-Benzo[d]imidazol-2-yl)ethanone with H2O2 - Shenggui Liu; Rongkai Pan; Guobi Li; Wenyi Su; Chunlin Ni (Journal of Chemistry)
A new ruthenium complex, Ru(bpbp)(pbb)Cl, based on 2,6-bis(1-(phenyl)-1H-benzo[d]imidazol-2-yl)pyridine (bpbp) and 2-(1-phenyl-1H-benzo[d]imidazol-2-yl)benzoate (pbb) was synthesized. The complex Ru(bpbp)(pbb)Cl could catalytically oxidize 1-(1H-benzo[d]imidazol-2-yl)ethanol to 1-(1H-benzo[d]imidazol-2-yl)ethanone with H2O2 as oxidant. Influence of temperature and catalyst amount on the oxidation reaction was evaluated. The reaction optimal conditions are as follows: molar ratio of catalyst to substrate to H2O2 is 1 : 1000 : 3000, the proper reaction temperature is 50°C and reaction time lasts 5 h, and the isolated yield of 1-(1H-benzo[d]imidazol-2-yl)ethanol to 1-(1H-benzo[d]imidazol-2-yl)ethanone under the optimal reaction conditions is 57%.